Global Pricing - Lestari, Indah; Nasution, Sabrina; Khoiri, Ahmad; Suhairi, Suhairi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Global pricing, also known as global price setting, is a pricing strategy that tries to unify the price of a product or service across all global markets. This concept involves making pricing decisions based on global factors such as economic conditions, market demand, international competition, and currency considerations. Global pricing enables companies to optimize profitability and be responsive to market differences, while addressing the complex challenges associated with the variation in the global business environment. The success of implementing this strategy depends on a deep understanding of the characteristics of the global market and the appropriate adaptation to dynamic changes in various regions.